Effect of EM4 (Effective Microorganism 4) on Growth and Productivity of Cucumber (Cucumis sativus L.) - Yuniati, Ratna; Damayanti, Margaretta Elsa; Wardhana, Wisnu (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractCucumber (Cucumis sativus L.) is a nutritious and healthy vegetable that is commonly consumed by Indonesian people. To fulfill self-sufficiency for household scale needs during the COVID-19 pandemic, cucumber cultivation can be carried out in home gardens, using containers such as polybags. Growing cucumbers on limited land requires a carefully optimized planting media composition by applying Effective Microorganism 4 (EM4) to the polybag media when planting. The research has been conducted which aims to determine the best EM4 dosage for the growth and productivity of cucumbers. The study used a Randomized Block Design consisting of control and three treatment doses of 10% concentration EM4, namely 20, 40, and 60 mL per polybag with six replications. The planting media used is a mixture of loam soil and goat manure. NPK fertilizer is given as an additional nutrient. The EM4 application is done by pouring it every eight days into the planting media in polybags. The results showed an increase in growth parameters and productivity of cucumber plants namely plant height, leaf chlorophyll content, time of flower emergence, number of flowers, and number of flowers that form fruit. 40 mL EM4 is the dose that showed the highest growth and productivity.AbstrakMentimun (Cucumis sativus L.) merupakan sayuran bergizi dan menyehatkan yang banyak dikonsumsi masyarakat Indonesia. Untuk memenuhi swasembada kebutuhan skala rumah tangga di masa pandemi COVID-19, budidaya mentimun dapat dilakukan di pekarangan rumah, dengan menggunakan wadah polybag. Menanam mentimun di lahan terbatas memerlukan optimalisasi komposisi media tanam secara cermat dengan menerapkan Effective Microorganism 4 (EM4) pada media dalam polybag. Telah dilakukan penelitian yang bertujuan untuk mengetahui dosis EM4 terbaik untuk pertumbuhan dan produktivitas tanaman mentimun. Penelitian menggunakan Rancangan Acak Kelompok yang terdiri atas kontrol dan tiga perlakuan dosis EM4 konsentrasi 10% yaitu 20, 40, dan 60 mL per polybag dengan enam ulangan. Media tanam yang digunakan adalah campuran tanah lempung dan kotoran kambing. Pupuk NPK diberikan sebagai unsur hara tambahan. Penerapan EM4 dilakukan dengan cara disiram setiap delapan hari sekali ke dalam media tanam di polybag. Hasil penelitian menunjukkan adanya peningkatan parameter pertumbuhan dan produktivitas tanaman mentimun yaitu tinggi tanaman, kandungan klorofil daun, waktu munculnya bunga, jumlah bunga, dan jumlah bunga yang membentuk buah. Dosis yang menunjukkan pertumbuhan dan produktivitas tertinggi adalah 40 mL EM4.